Hiistory of psychology - Hothersall, David (New York: Random House, 1984)
Contents: Psychology and the ancients. Philosophical and scientific antecedents of psycology. Nineteenth - century suties of the central nervous system. Wilhelm wundt and the founding of psychology. Edward Titchener and Hugo Munsterberg. Other German psuchologists of the eighteenth and nineteenth centuries. Gestalt psychology in Germany and the United States. The early history of clinical psychology and the United States. Forerunnes of fuctionalism in England and the United States
Includes bibliographical references and index
Keywords: Psicología - Historia